2012
DOI: 10.1111/j.1095-8649.2012.03335.x
|View full text |Cite
|
Sign up to set email alerts
|

Parasites as indicators of movement and population connectivity of a non‐diadromous, tropical estuarine teleost: king threadfin Polydactylus macrochir

Abstract: Temporal and spatial patterns in parasite assemblages were examined to evaluate the degree of movement and connectivity of post-recruitment life-history stages of a large, non-diadromous tropical estuarine teleost, king threadfin Polydactylus macrochir, collected from 18 locations across northern Australia. Ten parasites types (juvenile stages of two nematodes and seven cestodes, and adults of an acanthocephalan) were deemed to be suitable for use as biological tags, in that they were considered to have a long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 71 publications
(85 reference statements)
1
18
0
Order By: Relevance
“…The numbers of trypanorhynch metacestodes are generally positively correlated with fish age (e.g. Lester et al 2001; Moore et al 2011, 2012 a ) suggesting that long survival of metacestodes in fish may be a common phenomenon. One exception is Hepatoxylon trichiuri in albacore, Thunnus alalunga , which may not survive for the life of the fish (Jones, 1991).…”
Section: Case Studies From Australasia East Asia and Pacific Island mentioning
confidence: 99%
See 3 more Smart Citations
“…The numbers of trypanorhynch metacestodes are generally positively correlated with fish age (e.g. Lester et al 2001; Moore et al 2011, 2012 a ) suggesting that long survival of metacestodes in fish may be a common phenomenon. One exception is Hepatoxylon trichiuri in albacore, Thunnus alalunga , which may not survive for the life of the fish (Jones, 1991).…”
Section: Case Studies From Australasia East Asia and Pacific Island mentioning
confidence: 99%
“…Using many of the same parasite types, Moore et al (2012 a ) examined 990 individual P. macrochir among 18 locations across northern Australia, as part of a multidisciplinary study into the movement and stock structure of the species. They found that while fish from most locations generally harboured different parasite faunas, suggesting the existence of a mosaic of stocks across northern Australia, fish from the south-eastern Gulf of Carpentaria were found to share a similar parasite fauna over spatial scales of up to 500 km.…”
Section: Case Studies From Australasia East Asia and Pacific Island mentioning
confidence: 99%
See 2 more Smart Citations
“…Neoechinorhynchus topseyi Podder, 1937, now identified as N. vittiformis Smales, 2013, and Raosentis sp. were reported from Eleutheronema tetradactylum (Shaw), although whether they were collected in both the eastern coast of Queensland and the Gulf of Carpentaria was not indicated (Moore et al, 2012, Smales, 2013. In addition, 2 species have been reported from the Gulf of Carpentaria.…”
mentioning
confidence: 99%